Development of Multiple-Unit Floating Drug Delivery System of Clarithromycin: Formulation, in vitro Dissolution by Modified Dissolution Apparatus, in vivo Radiographic Studies in Human Volunteers - Reddy, Arun B.; Reddy, Narendar D. (Drug Research, 2017)
Clarithromycin (CM), a broad spectrum macrolide antibiotic used to eradicate H. pylori in peptic ulcer. Clarithromycin (CM) is well absorbed from the gastrointestinal tract, but has a bioavailability of 50% due to rapid biodegradation. The aim of this investigation was to increase the gastric residence time, and to control the drug release of clarithromycin by formulating into multiple unit floating mini-tablets. Floating tablets were prepared by using direct compression method with HPMC K4M and Polyox WSR 1105 as release retarded polymers and sodium bicarbonate as gas generating agent. The prepared mini-tablets were evaluated for thickness, weight variation, friability, hardness, drug content, in vitro buoyancy, swelling studies, in vitro dissolution studies by using modified Rossett-Rice test and in vivo radiographic studies in healthy human volunteers in fasting conditions. DSC analysis revealed that no interaction between drug and excipients. All the physical parameters of the tablets were within the acceptable limits. The optimized formulation (F6) had showed controlled drug release of 99.16±3.22% in 12 h, by zero-order release kinetics, along with floating lag time of 9.5±1.28 s and total floating time of 12±0.14 h. X-ray imaging studies revealed that in vivo gastric residence time of clarithromycin floating mini-tablet in the stomach was about 3.5 h. The results demonstrated that the developed floating mini-tablets of clarithromycin caused significant enhancement in gastric retention time along with sustained effect and increased oral bioavailability.
Keywords: H. Pylori; clarithromycin; floating mini tablets; in vitro release; X-ray study